2015
DOI: 10.1007/s00284-015-0804-z
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Semiquantitative Analysis of Fecal Bifidobacterium Species in Centenarians Living in Bama, Guangxi, China

Abstract: Centenarians constitute a significant subpopulation in the Bama County of Guangxi province in China. The beneficial effects of intestinal microbiota, especially bifidobacteria of centenarians, have been widely accepted; however, knowledge about Bifidobacterium species in centenarians is not adequate. The aim of this study was to investigate the quantity and prevalence of fecal Bifidobacterium in healthy longevous individuals. Fecal samples from eight centenarians from Bama (aged 100 to 108 years), eight younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
1
15
1
1
Order By: Relevance
“…Previous study reported the detection of B. gallinarum/B. pullorum / B. saecularmay, B. minimum and B. mongoliense in Chinese centenarian [39]. However, these species were not detected in the five Japanese centenarians in the present study.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Previous study reported the detection of B. gallinarum/B. pullorum / B. saecularmay, B. minimum and B. mongoliense in Chinese centenarian [39]. However, these species were not detected in the five Japanese centenarians in the present study.…”
Section: Discussioncontrasting
confidence: 80%
“…These adult-type predominant Bifidobacterium species persisted in elderly, with an increase in the prevalence of B. dentium species [8, 21, 28]. Recently, Wang et al [39] revealed that the faecal Bifidobacterium species in centenarians of Chinese descent were different from those of young elderlies. Despite the common faecal Bifidobacterium species, including B. dentium , B. longum ssp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P < 0.05. glycolytic enzyme essential for GOS metabolism that typically is genetically linked with a LacS permease responsible for transport and internalization of GOS (6). B. dentium has been less thoroughly characterized, is mostly associated with the oral cavity, and recently was shown to be increased in the stools of 100-to 108-y-old centenarians living in Bama, Guangxi (China) as compared with younger (80-to 99-y-old) elderly persons (19).…”
Section: Discussionmentioning
confidence: 99%
“…A further decline is then seen as we enter the elderly phase of life [35], which interestingly also correlates to a decrease in immune function, so-called immunosenescence. Exactly when or why this happens is still unclear, but higher bifidobacteria levels in the elderly are correlated with health and longevity [36,37].…”
Section: Bifidobacterium Across the Life Coursementioning
confidence: 99%